Design of a Low Cost Heartbeat Monitoring System - Vishnu Vardhan Reddy, Bana; R., Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
This project shows the importance of the heartbeat sensor to a person. A heartbeat sensor is important to know the pathological condition of a person. It can provide a real-time heartbeat measurement and notify us if an oddity occurs in the heartbeat. We can develop a vital sign detection system using a microcontroller and sensors. This project presents a prototype to monitor heartbeat rate. It senses the heartbeat and converts the signal into electrical signals. This signal is amplified by the circuit. Our aim is to provide a simple and robust method to detect heartbeat. The model is accurate and cheaper than other models. The fatal accident rate has increased over the past decade, so a monitoring system will be a lot helpful to everyone and save lives.